Relationship between Vascular Risk Factors and Location of Intracranial Atherosclerosis in the SAMMPRIS Trial - Almallouhi, Eyad (J Stroke Cerebrovasc Dis, 2020)
BACKGROUND: Previous studies have reported that different locations of intracranial atherosclerosis (ICAS) are associated with different demographic features and vascular risk factors. We aimed to examine this observation in the Stenting and Aggressive Medical Management for Preventing Recurrent stroke in Intracranial Stenosis (SAMMPRIS) trial population. METHODS: SAMMPRIS was a randomized controlled trial that enrolled 451 patients with recent transient ischemic attack or stroke-related due to severe (70-99%) stenosis of a major intracranial artery. We compared the baseline demographic features and vascular risk factors between the symptomatic artery locations. Wilcoxon test was used to compare continuous variables, and chi-square test was used for categorical variables. RESULTS: Of 449 patients included in the analysis; 289 (64.4%) had ICAS in the anterior circulation and 160 (35.6%) in the posterior circulation. Features that were significantly different between patients with anterior versus posterior ICAS were: median age (58.3 years vs. 64.0 years, P<0.001), males / females (52.9% / 47.1% vs. 74.4% / 25.6% P<0.001), white / black (66.8% / 26.6% vs. 79.4% / 16.9%, P=0.02), and history of hyperlipidemia (85.5% vs. 92.5%, P=0.03). CONCLUSION: The observed differences in the distribution of demographic characteristics and vascular risk factors depending on the location of symptomatic ICAS suggest the possibility of different underlying pathological processes involved in the formation of atherosclerotic plaques in different locations.